Sequence rearrangement and duplication of double stranded fibronectin cDNA probably occurring during cDNA synthesis by AMV reverse transcriptase and Escherichia coli DNA polymerase I. - Fagan, J B (1980)
Two cloned cDNAs derived from the mRNA for cell fibronectin have been sequenced, providing evidence that transcription with AMV reverse transcriptase or Escherichia coli DNA polymerase I may not always result in double stranded cDNA that is exactly homologous with its mRNA template. Instead, the sequences of these cloned cDNAs are consistent with the duplication and rearrangement of sequences during synthesis of double stranded cDNA.